دور حجم رأس المال في نسبة الرفع المالي والمخاطر لتحقيق السلامة البنكية وفق بازل 3 - زرمان، توفيق (جامعة الوادي University of Eloued, 2025)
تهدف هذه الدراسة الى معرفة دور حجم رأس المال في نسبة الرفع المالي، لتفادي المخاطر وتحقيق السلامة البنكية، وقد حددت نسبة الرفع المالي تساوي او تفوق 3% وفق بازل 3، لهذا على البنك كذلك تحديد إجمالي الأصول المعرضة للمخاطر كمتغير أساسي، وقد اعتمدنا على المنهج الوصفي التحليلي لوصف وتحليل المعطيات المتعلقة بمتغيرات الدراسة، ثم المنهج الإحصائي من خلال تتبع سلسلة زمنية مكونة من خمس سنوات لتغير نسبة الرفع المالي، مع الإشارة الى حالة بنك سوسيتيه جنرال 2019-2023. وقد توصلنا الى نتائج مفادها أن تغير حجم رأس المال الأساسي او تغير اجمالي الأصول المعرضة للمخاطر لها دور إما إيجابا أو سلبا على نسبة الرفع المالي، فاذا ارتفع حجم رأس المال فان نسبة الرفع المالي ستزيد بمعنى هناك علاقة طردية، اما إذا زاد اجمالي الأصول فان نسبة الرفع المالي سوف تنخفض بمعنى هناك علاقة عكسية، وبالتالي على البنك اختيار الحجم الأمثل لرأس المال والأصول This studyaims to examine the role of capital size in the financialleverage ratio to mitigaterisks and achievebankingstability. According to Basel III, the financialleverage ratio is set at 3% or higher. Therefore, the bank must alsodetermine the total riskweightedassets as a key variable.The studyadopts a descriptive-analyticalapproach to describe and analyze data related to the study variables, alongwith astatisticalapproach by tracking a time series over five years to observe changes in the financialleverage ratio, focusing on the case of Société Générale Bank from 2019 to 2023.The findingsindicatethat changes in core capital size or total riskweightedassetscan have either a positive or negative impact on the financialleverage ratio. If the capital size increases, the financialleverage ratio willrise, indicating a direct relationship. Conversely, if total assetsincrease,the financialleverage ratio willdecline, indicating an inverse relationship. Therefore, the bank must determine the optimal size of capital and assets.
The Role of Capital Size in the Financial Leverage Ratio and Risks to Achieve Banking Stability According to Basel III: The Case of SociétéGénérale Bank During 2019-2023.
Keywords: رأس المال; الرفع المالي; المخاطر; السلامة البنكية; بازل3; Capital; financialleverage; risk; bankingstability; Basel III.